Gluten free diet adherence in coeliac disease. The role of psychological symptoms in bridging the intention–behaviour gap - Sainsbury, K.; Mullan, Barbara; Sharpe, L. (Elsevier BV, 2013)
This study examined the potential role of psychological symptoms in limiting the translation of positive intention into strict gluten free diet (GFD) adherence in coeliac disease (CD) within a theory of planned behaviour (TPB) framework. It was hypothesised that participants with more symptomatic psychological profiles would exhibit poorer adherence, primarily in the context of positive intentions. Coeliac disease participants (N = 390) completed online measures of gluten free diet adherence, psychological symptoms, coping behaviour, and TPB items. Intention and behaviour were moderately correlated, confirming the existence of the intention–behaviour gap. Psychological symptoms accounted for additional variance over and above TPB variables in GFD adherence but not intention. Participants who failed to act on their positive intentions displayed more psychological symptoms and greater reliance on maladaptive coping strategies than those with consistent intention–behaviour relationships (p < .01). The heightened incidence of psychological symptoms in CD has a small but significant negative impact on the ability to translate positive intentions into strict adherence. Directions for future research including interventions to improve GFD adherence are discussed.